Iceland : Technical Assistance Report. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Assistance report on Iceland discusses that the issue of maintaining alignment with budgets and budgetary reports that are expected to focus on Government Finance Statistics Manual of 2001 (GFSM 2001) indicators. Consolidated 'whole-of-government' financial statements of the central government will facilitate fiscal policy informed by a broader view of public finances. Recognition and systematic accounting of physical assets are expected to enhance transparency and facilitate management and budgetary decisions. Under the current framework such assets-including roads, bridges, tunnels, land, and buildings-are treated as expenses and written off in the year in which they are acquired. Some changes in valuation of financial assets and liabilities may also be required. The cash flow statement should provide information about key revenues and expenditures. The budget should recognize depreciation as an expense but need not appropriate for depreciation at this stage. The budgeted operating statement should include depreciation as an expense to determine the operating result.